Geochemistry and Irrigation Quality of Groundwater along River Jhelum in South Kashmir, India - R. Yousuf1, Akbar Masood2; Aabid Hussain Naqash1, Arshid Jehangir1*, Aasimah Tanveer1, A. (Recent Research in Science and Technology, 2011)
A preliminary investigation was made to understand the geochemical characteristics of ground water sources in South Kashmir Jhelum River basin. A total of twenty ground water samples, representing shallow and deep sources were collected and analyzed for different geochemical parameters. The studied ground water sources have generally high alkalinity and hardness owing to the lacustrine deposits in the valley. The dominance pattern of cations in the studied ground water was as follows: Ca>Mg>Na>K and the sequence of anionic dominance was as follows: HCO3> Cl > SO4. The study showed that the regional geology as well as rock water interactions has played a dominant role in determining the concentration of various ions in ground water aquifers. In certain aquifers chloride concentration was fairly high and can be attributed to anthropogenic pressure, as there is less predominance of chloride bearing minerals. This study further envisages that these ground water aquifers have low Sodium adsorption ratio and %Na hence are fit for irrigation, while residual sodium carbonate and salinity values indicated that majority of these aquifer have water of marginal to harmful quality for irrigation purposes.